2015
DOI: 10.3389/fphar.2015.00162
|View full text |Cite
|
Sign up to set email alerts
|

The role of the serotonin receptor subtypes 5-HT1A and 5-HT7 and its interaction in emotional learning and memory

Abstract: Serotonin [5-hydroxytryptamine (5-HT)] is a multifunctional neurotransmitter innervating cortical and limbic areas involved in cognition and emotional regulation. Dysregulation of serotonergic transmission is associated with emotional and cognitive deficits in psychiatric patients and animal models. Drugs targeting the 5-HT system are widely used to treat mood disorders and anxiety-like behaviors. Among the fourteen 5-HT receptor (5-HTR) subtypes, the 5-HT1AR and 5-HT7R are associated with the development of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(67 citation statements)
references
References 158 publications
(188 reference statements)
1
66
0
Order By: Relevance
“…Indeed, deciphering the effects of serotonin (5-hydroxytryptamine, or 5-HT) on sleep is a complex matter, especially since this monoamine neurotransmitter plays major roles in several physiological functions including appetite, gastrointestinal motility, thermoregulation, nociception, emotion and cognition (Artigas, 2015;Berger et al, 2009;Stiedl et al, 2015). Moreover, 5-HT effects are mediated by a wide family of receptors that are classified into seven main receptor subtypes, designated 5-HT 1e7 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, deciphering the effects of serotonin (5-hydroxytryptamine, or 5-HT) on sleep is a complex matter, especially since this monoamine neurotransmitter plays major roles in several physiological functions including appetite, gastrointestinal motility, thermoregulation, nociception, emotion and cognition (Artigas, 2015;Berger et al, 2009;Stiedl et al, 2015). Moreover, 5-HT effects are mediated by a wide family of receptors that are classified into seven main receptor subtypes, designated 5-HT 1e7 .…”
Section: Introductionmentioning
confidence: 99%
“…Agonist PET probes would also be desirable when assessing the association between 5-HT 1A receptors and behavioral phenotypes. The involvement of the 5-HT 1A receptor in various aspects of cognition, depression, and anxiety has been amply demonstrated (Harder and Ridley, 2000; Gingrich and Hen, 2001; Albert et al, 2014; Stiedl et al, 2015), but a human database of 5-HT 1A receptor binding by PET with an antagonist probe 11 C-WAY100635 showed high between-subject variability and failed to find any correlations with personality variables (Rabiner et al, 2002), while several studies reported an association with anxious or aggressive traits in smaller sample sizes (Tauscher et al, 2001; Parsey et al, 2002). …”
Section: Discussionmentioning
confidence: 99%
“…31,[58][59][60][61][62] The observed reduction in anxiety associated with pharmacologic inhibition, or receptor inactivation using knockout mouse models, suggests that both the 5-HT 1A and 5-HT 7 receptors may mediate anxiety symptoms and behaviors. 58,62 Previous studies have reported that the presence of prominent anxiety in MDD was associated with increased illness severity and functional impairment.…”
Section: Lurasidone For Mdd With Mixed Features and Anxiety 241mentioning
confidence: 99%